Włodzimierz Staniewski and the phenomenon of "Gardzienice" - Gontarski, S. E.; Kręglewska, Katarzyna; Wiśniewski, Tomasz (Routledge advances in theatre and performance, 2022)
"This book offers a broad overview of the contemporary state of the Gardzienice theatrical company and its evolution. Their most recent production, The Wedding, is taken as a focal point for a retrospective discussion on the company's development. Premiered at the festival celebrating the 40th anniversary of the company, The Wedding echoes most of the major achievements of Staniewski's stage language and his capacity of exploring and developing the performative potential of liveness. This study consists of essays by prominent practitioners and theoreticians of theatre, director's notes, conversations with Staniewski and other company members, selected archival materials and substantial visual coverage. It promises to be of great interest to students and scholars across the fields of theatre and performance studies"--